2011
DOI: 10.2341/11-013-l
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Novel At-home Bleaching Technique With Carbamide Peroxides Modified by CPP-ACP and Its Effect on the Microhardness of Bleached Enamel

Abstract: This study was designed to evaluate in vitro the efficacy of a novel at-home bleaching technique using 10% or 16% carbamide peroxide modified by casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) and its influence on the microhardness of bleached enamel. A total of 40 bovine incisors were divided into four groups (n=10) according to the bleaching agent used: 10% carbamide peroxide only; a blend of 10% carbamide peroxide and a CPP-ACP paste; 16% carbamide peroxide only; and a blend of 16% carbamide per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 25 publications
1
57
0
5
Order By: Relevance
“…These deposits may have acted as a physical barrier, minimizing the contact of the acid to enamel, or providing additional mineral to be dissolved during the acid challenge before the underlying enamel was attacked. Another forms of calcium combined with bleaching agents have been previously investigated, such as the casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) [39, 40] and calcium chloride [12], resulting in increased mechanical properties of bleached enamel.…”
Section: Discussionmentioning
confidence: 99%
“…These deposits may have acted as a physical barrier, minimizing the contact of the acid to enamel, or providing additional mineral to be dissolved during the acid challenge before the underlying enamel was attacked. Another forms of calcium combined with bleaching agents have been previously investigated, such as the casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) [39, 40] and calcium chloride [12], resulting in increased mechanical properties of bleached enamel.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, HP supplemented with Ca was shown to be the most effective modified gel tested. Different forms of calcium have been added to bleaching gels, in an attempt to increase the chemical properties of bleached enamel [5,29]. The presence of calcium in the gel is expected to maintain the enamel calcium saturation during bleaching [6].…”
Section: Discussionmentioning
confidence: 99%
“…Boersma et al investigated the prevalence of white spot lesions (WSL) at the end of orthodontic treatment by using the QLF (Quantitative Light-induced Fluorescence) technique and found that 97% of the subjects had one or more lesions [4]. For many years, dentistry was influenced by a mechanical approach characterized by the use of high-speed rotary cutting instruments and radical removal of diseased portions of the tooth, along with material-driven geometric extensions to areas that were assumed to be caries-resistant [5]. In all areas of medicine, there is a desire for less invasive, early protective and preventive procedures.…”
Section: Introductionmentioning
confidence: 99%